Analysis of delays in Tanzanian construction industry: Transaction cost economics (TCE) and structural equation modeling (SEM) approach - T.J., Deepak; Ponniah, Venishri (Emerald Publishing Limited, 2017)
Purpose The purpose of this paper is twofold: first, to develop theoretical underpinnings using TCE, and second, to run the analysis using an advanced tool such as structural equation modeling (SEM).